IMPACT OF RESTORATIVE MATERIAL ON FRACTURE STRENGTH OF ROOT CANAL TREATED TEETH: AN IN VITRO STUDY - Hasan, Syeda Rida; Muneeb Lone, Maham; Rana, Aushna Khushbakht; Abidi, Yawar Ali (Journal of Ayub Medical College Abbottabad, 2023)
Background: There are a number of materials available in the market for the core buildup of endodontically treated teeth. The purpose of our study is to evaluate the fracture resistance of endodontically treated teeth restored with composite resin, amalgam and glass ionomer cement as core buildup materials. Methods: Forty-eight sound-extracted mandibular premolar teeth were randomly divided into 4 groups of 12 teeth each. The first group served as a control and consisted of intact sound teeth. In all of the remaining teeth, root canal treatment was performed first. In Group II composite resin was used as the core build-up material Group III amalgam and Group IV GIC. Teeth were then subjected to fracture using a universal testing machine. Results: One Way ANOVA test was performed to study the differences in the data of the four groups. The mean forces required for fracture were 1050 N for control teeth, 738 N for composite, 872 N for amalgam and 567 N for GIC. The variation is of statistical significance as depicted by a p-value of 0.003. Conclusion: The highest strength was shown by intact sound teeth. Teeth restored with composite resin and amalgam had similar strengths and those with GIC had significantly lower resistance to fracture.